Forging power - "Chakrabarty, Bidyut" (New Delhi, 2006)
This book looks at the evolution of coalition politics in India, both at the national and provincial levels, with the modern Indian polity having emerged as an example of the phenomenon par excellence. This has come about in spite of the commonly held views of the Indian political experience as a single dominant party system splintering into a multi-party coalition. Not only was the Congress Party a social as well as ideological coalition, even the cabinet government in the initial post-independence years was constituted on coalition principles. The book argues that the bulk of the Indian party system emerged due to a gradual erosion of this coalition. It studies the 1970s and 1980s when the Indian electorate experimented with coalition and one-party rule. The 1990s and 2000s have nurtured the coalition culture in India, with the NDA and UPA governments gaining power. The author argues that in a socio-culturally diverse country like India, coalition rule is inevitable as the melt in g pot logic has lost its viability and single-party rule is a myth. The book, while studying the phenomenon from available theoretical perspectives, explains that these are insufficient to articulate the Indian experience. Thus new theoretical models grounded on the present Indian socio-economic reality are required.
Keywords: Coalition Politics-India